Determinan Literasi Ekonomi pada Mahasiswa Program Studi Ekonomi Pembangunan UIN Syarif Hidayatullah Jakarta - Fitri Amalia; Indah Eka Pratiwi (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
Economic literacy is very important for life, because the higher our level of economic literacy, the better we are at dealing with problems and finding solutions regarding the economy. This research was conducted to see what factors can increase the economic literacy of Development Economics students. With the research location at the Syarif Hidayatullah State Islamic University (UIN) Development Economics Study Program, Jakarta. The method used is survey and analyzed using ordinary least square multiple linear regression. The study used primary data by distributing questionnaires to 159 students of the Development Economics Study Program who had received courses in micro and macro economic theory. The sampling technique used is simple random sampling using the Slovin formula. The results showed that the variables of parents' occupation, parents' income, mother's education and gender influenced economic literacy. While the variables of e-wallet ownership and learning achievement do not significantly affect economic literacy.